Perlindungan Hukum Terhadap Masyarakat Terdampak Pencemaran Air Akibat Kegiatan Tambang - Marco; Jocelyne Tika Budianto; Nova Ratu Sabina (SYARIAH : Jurnal Ilmu Hukum, 2025)
This study analyzes legal protections for communities affected by water pollution from coal mining in Indonesia, where regulatory frameworks (e.g., Law No. 32/2009, Law No. 4/2009) exist but fail due to weak enforcement and corporate dominance. Using normative legal methods and qualitative case studies from South Kalimantan and South Sumatra, it reveals systemic gaps: inadequate sanctions, bureaucratic inefficiencies, and marginalized community access to justice. Findings show severe ecological and health impacts (e.g., toxic water, livelihood loss) with legal remedies often ineffective, as seen in protracted court cases and minimal corporate accountability. The study concludes that harmonizing regulations, strengthening sanctions, and empowering communities are critical to achieving environmental justice, urging reforms to align mining practices with sustainable development goals.